Very Late Patent Foramen Ovale Occluder Device Structural Dysfunction and Thrombosis - Rami M. Abazid, MD; Osama Smettei, MD; Jasmin Nari; Sabe De; Andrew Mathew; Kumar Sridhar; Guo Lin-Rui Ray, MD; Nikolaos Tzemos, MD (JACC: Case Reports, 2024)
Mechanical dysfunction of patent foramen ovale (PFO) closure device is extremely rare. We present a 58-year-old male patient who had multiple episodes of ischemic strokes 3 years after PFO closure, which was related to PFO device mechanical dysfunction and thrombosis. He was successfully treated with surgical intervention.